Problem: Consider the following chemical equation:AaBb(s) → a A+ (aq) + b B- (aq)In this case, the Ksp is given by:a. Ksp = a [A+] b [B-]b. Ksp = ([A+] / a) ([B-] / b)c. Ksp = [A+] [B-] / [AaBb]d. Ksp = [A+]a [B-]be. Ksp = [A+]a [B-]b / [AaBb]

FREE Expert Solution

We are provided with a chemical equation and we have to write the Ksp expression.

Ksp is called the solubility product and is it is an equilibrium constant for substances that dissociate in aqueous solutions.

Ksp is written just like an equilibrium constant:

K = ProductsReactants

79% (106 ratings)
Problem Details

Consider the following chemical equation:

AaBb(s) → a A(aq) + b B(aq)

In this case, the Ksp is given by:

a. Ksp = a [A+] b [B-]

b. Ksp = ([A+] / a) ([B-] / b)

c. Ksp = [A+] [B-] / [AaBb]

d. Ksp = [A+]a [B-]b

e. Ksp = [A+]a [B-]b / [AaBb]

Frequently Asked Questions

What scientific concept do you need to know in order to solve this problem?

Our tutors have indicated that to solve this problem you will need to apply the Ksp concept. You can view video lessons to learn Ksp Or if you need more Ksp practice, you can also practice Ksp practice problems .